2021
DOI: 10.1016/j.xcrm.2021.100471
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic analysis identifies CPT1A as a potential therapeutic target in platinum-refractory, high-grade serous ovarian cancer

Abstract: Summary Resistance to platinum compounds is a major determinant of patient survival in high-grade serous ovarian cancer (HGSOC). To understand mechanisms of platinum resistance and identify potential therapeutic targets in resistant HGSOC, we generated a data resource composed of dynamic (±carboplatin) protein, post-translational modification, and RNA sequencing (RNA-seq) profiles from intra-patient cell line pairs derived from 3 HGSOC patients before and after acquiring platinum resistance. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 190 publications
(252 reference statements)
4
30
0
Order By: Relevance
“…This would be particularly relevant in OC, since it has been extensively demonstrated that OXPHOS plays a relevant role in this tumor type compared to most cancers [ 50 ]. Accordingly, a recent multi-omic profiling of the same platinum-resistant and sensitive OC cell models used in the present study highlighted that OXPHOS and fatty acid oxidation are implicated in platinum resistance [ 28 ]. In recent years, evidence has been accumulating on the relevance of lipid metabolism in disease progression and acquisition of chemoresistance in OC [ 29 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be particularly relevant in OC, since it has been extensively demonstrated that OXPHOS plays a relevant role in this tumor type compared to most cancers [ 50 ]. Accordingly, a recent multi-omic profiling of the same platinum-resistant and sensitive OC cell models used in the present study highlighted that OXPHOS and fatty acid oxidation are implicated in platinum resistance [ 28 ]. In recent years, evidence has been accumulating on the relevance of lipid metabolism in disease progression and acquisition of chemoresistance in OC [ 29 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, metastatic OC cells in the omentum, growing in close proximity with adipocytes, enhance fatty acid uptake, by upregulating fatty acid receptor CD36, and utilization via β-oxidation, by upregulating the expression of CPT1A, leading to an increase in OXPHOS activity [ 25 , 26 ]. Notably, inhibition of both OXPHOS and β-oxidation improves the sensitivity of OC cells to platinum compounds [ 27 , 28 ]. In line with this evidence, we have previously demonstrated that drug resistant OC cells rely on OXPHOS for their energetic metabolism and that increased mitochondrial respiration is responsible for the chemoresistant phenotype by promoting the activation of a pro-inflammatory program [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPT1A catalyzes the rate-limiting step of the fatty acid oxidation (FAO) pathway, promoting cell proliferation and suppressing apoptosis (42). Abnormal CPT1A expression was associated with the poor OS of AML (43), ovarian cancer (44), and glioblastoma stem cells (45). Leslimar et al reported that CPT1A could regulate prostate cancer survival in hypoxic conditions and promote aggressiveness (46).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the pipeline consists of two major steps. We first derive prior information on causal protein-protein interactions using a time-course ovarian cancer cell line proteogenomic data set from a treatment perturbation experiment (Step 1) [26]. Then, using the direction information learned from Step 1 as priors, we construct an outcome-driven-DAG for genes in the Oxidative Phosphorylation and Adipogenesis pathways using a tumor proteogenomic data set from the CPTAC retrospective ovarian (Retro-Ova) cancer study (Step 2) [3].…”
Section: Application To Ovarian Cancermentioning
confidence: 99%